Using the Multidimensional Prognostic Index (MPI) to improve cost-effectiveness of interventions in multimorbid frail older persons: results and final recommendations from the MPI_AGE European Project - Cruz-Jentoft, Alfonso J; Daragjati, Julia; Fratiglioni, Laura; Maggi, Stefania; Mangoni, Arduino A; Mattace-Raso, Francesco; Paccalin, Marc; Polidori, Maria Cristina; Topinkova, Eva; Ferrucci, Luigi; Pilotto, Alberto (Aging Clinical and Experimental Research, 2020)
MPI_AGE is a European Union co-funded research project aimed to use the Multidimensional Prognostic Index (MPI), a validated Comprehensive Geriatric Assessment (CGA)-based prognostic tool, to develop predictive rules that guide clinical and management decisions in older people in different European countries. A series of international studies performed in different settings have shown that the MPI is useful to predict mortality and risk of hospitalization in community-dwelling older subjects at population level. Furthermore, studies performed in older people who underwent a CGA before admission to a nursing home or receiving homecare services showed that the MPI successfully identified groups of persons who could benefit, in terms of reduced mortality, of specific therapies such as statins in diabetes mellitus and coronary artery disease, anticoagulants in atrial fibrillation and antidementia drugs in cognitive decline. A prospective trial carried out in nine hospitals in Europe and Australia demonstrated that the MPI was able to predict not only in-hospital and long-term mortality, but also institutionalization, re-hospitalization and receiving homecare services during the one-year follow-up after hospital discharge. The project also explored the association between MPI and mortality in hospitalized older patients in need of complex procedures such as transcatheter aortic valve implantation or enteral tube feeding. Evidence from these studies has prompted the MPI_AGE Investigators to formulate recommendations for healthcare providers, policy makers and the general population which may help to improve the cost-effectiveness of appropriate health care interventions for older patients.
Keywords: Male; multimorbidita; Cost-Benefit Analysis; Risk Factors; prognóza; hospitalizace; samostatný způsob života; analýza nákladů a výnosů; Aged; Prospective Studies; mužské pohlaví; senioři; křehký senior; Independent Living; geriatrické hodnocení; senioři nad 80 let; lidé; ženské pohlaví; Frail Elderly; Humans; Hospitalization; rizikové faktory; Aged, 80 and over; Prognosis; Female; Multimorbidity; Geriatric Assessment; prospektivní studie